Rapid Recovery From Cortical Blindness Caused by an Old Cerebral Infarction - Shibuki, Katsuei; Wakui, Ichiro; Fujimura, Takeo; Tomikawa, Masaru; Hasegawa, Shin (Frontiers in Neurology, 2020)
When the primary visual cortex (V1) is damaged, cortical blindness results. However, visual information obtained from the superior colliculus (SC) produces unconscious visual functions called blindsight. Alarming visual stimuli suggesting the approach of a predator are known to trigger escape behaviors via visual information mediated by the SC and amygdala, and also produce some conscious visual experience even in patients with blindsight. Fresh cortical blindness sometimes recovers spontaneously in patients with fresh cerebral damages, and recovery can be accelerated by early rehabilitation. However, the mechanisms underlying recovery are not well-known. We analyzed a patient with cortical blindness caused by an old cerebral infarction. After repeated presentation of alarming visual stimuli, the ability to detect visual stimuli in the impaired visual field showed short-term potentiation (STP) within a few minutes. Repeated STP induction was followed by long-term potentiation (LTP) lasting more than several days. After LTP, the patient partially recovered the ability to read letters presented in the impaired visual field. The STP experiment, which can be performed within 10 minutes, may serve as a clinical screening test for anticipating recovery from cortical blindness.